The Effect of Tax Morals and the Digitalized Tax System on Tax Compliance with Trust in the Government as a Moderating Variable - Sulistyono, Henry; Ratna Mappanyukki (Dinasti Publisher, 2023)
The purpose of this research was to determine the effect of tax morale and tax digitalization system on tax compliance with trust in government as a moderating variable. The population in this study are corporate taxpayers in the Cikarang-Cibitung Industrial Area. In this study the data analysis technique used was quantitative using the PLS-SEM (Structural Equation Model) or structural equation model. The results of this research were Tax Morale has no effect on Taxpayer Compliance, The Tax Digitization System has a positive influence on Taxpayer Compliance, Trust in the Government in this study cannot act as a moderating variable in the Tax Morale variable on Taxpayer Compliance, and Trust in the Government in this study cannot act as a moderating variable in the Tax Digitalization System variable on Taxpayer Compliance.